2019
DOI: 10.18203/2394-6040.ijcmph20192617
|View full text |Cite
|
Sign up to set email alerts
|

Maternal risk factors and its association with low birth weight: a study from rural area of Maharashtra

Abstract: Background: Low birth weight is single most important factor determining the survival chances of the child. A high percentage of low birth weight points to deficient health status of pregnant women, inadequate prenatal care and the need for improved care of the newborn. Present hospital based study was undertaken to identify the maternal risk factors associated with low birth weight babies.Methods: The present hospital based descriptive study was conducted at Swami Ramanand Teerth Rural Govt. Medical College a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Digole et al in their study showed the percentage decreased to 19.83% and 15.38% when pregnancy interval was increased to 2 and 3 or more. A significant association was found between pregnancy interval and birth weight of baby (p<0.05) [23].…”
Section: Discussionmentioning
confidence: 89%
“…Digole et al in their study showed the percentage decreased to 19.83% and 15.38% when pregnancy interval was increased to 2 and 3 or more. A significant association was found between pregnancy interval and birth weight of baby (p<0.05) [23].…”
Section: Discussionmentioning
confidence: 89%